Prototipe Rekam Kesehatan Personal pada Pasien Diabetes Mellitus (Literature Review) - Risma Ayu Fitriyani; Noor Yulia; Puteri Fannya; Laela Indawati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Personal Health Record (PHR) is a collection of health-related data that is archived and managed by an individual or parties associated with the PHR. Its purpose is to provide a comprehensive and accurate summary of a person's health history that can be accessed online. This research is a Literature Review study which aims to determine the features and implementation of Personal Health Records in Patients with Diabetes Mellitus. The method used is the Literature Review method from 7 journals which uses several methods including the prototype method, qualitative methods, heuristic evaluation methods, applied development methods, participatory action research methods, and randomized controlled trial methods with data collection techniques through google scholar, direct science and pubmed. The results of the research are seen in the features and implementation of the Personal Health Record. The Personal Health Record feature for diabetes mellitus with dialysis measures has 25 features on the main page, the PHR feature for diabetes mellitus has 7 main features. PHR implementation allows users to access their personal health records anytime and anywhere. Thus, the PHR system can increase accessibility and allow users to access PHR without time restrictions and also the Personal Health Record can assist in monitoring the health condition of Diabetes Mellitus patients. Research conclusion According to the journals analyzed, PHR is effective because it can encourage patient participation in individual health controls, and can access information about diabetes mellitus through monitoring physical activity, diet, weight, and glucose levels.